Pengembangan Bahan Ajar Berbasis Radec Read, Answer, Discuss, Explain, Create) Pada Mata Pelajaran IPAS Kelas V SD/MI - Desca Rio Takbirul Fitri; Nurul Hidayah; Yudesta Erfayliana (Mathematics Education Study Program, 2025)
This research is motivated by the limited variety of teaching materials and learning resources used in the classroom as well as the suboptimal use of technology. During the learning process, students generally relied only on the thematic textbooks provided by the school, while teachers occasionally used pre-prepared PowerPoint presentations. This condition made students less enthusiastic in learning. The purpose of this study is to develop flipbook-based teaching materials using the RADEC (Read, Answer, Discuss, Explain, Create) model for the IPAS subject on the topic of light and vision for fifth grade elementary school students, and to examine their feasibility and the responses of both students and teachers. The research employed the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The results show that the flipbook-based teaching material with the RADEC model is feasible to use. Validation by material experts obtained an average score of 90%, media experts 90%, and language experts 93%. Teachers’ responses reached 93%, while students’ responses averaged 90%. Therefore, the flipbook-based teaching material developed with the RADEC model is considered feasible, effective, and attractive for use in the learning process.